“My dear, lovely Gabriele!ʺ Alexander von Humboldt’s correspondence with his niece Gabriele von Bülow - Leitner, Ulrike (HiN - Alexander von Humboldt im Netz. Revue internationale d'études humboldtiennes, 2025)
Alexander von Humboldt’s correspondence with his niece Gabriele von Bülow, published in a book, comprising more than 450 letters (including many first publications), reflects the last third of Humboldt’s life, his scholarly work and publications, public activities at the Prussian Royal Court and in the Academies of Sciences and Arts, trips to Paris and commuting between Berlin and Potsdam – a sociable life among friends and family. The letters (almost exclusively from Humboldt, with only a few from Gabriele) occupy a special position among the scholar’s numerous correspondences because of their familial nature. Humboldt provides his niece with the latest news from Court, his circle of acquaintances and political life, and Gabriele takes a lively interest in his work.